早期負荷法による下顎インプラントオーバーデンチャー症例 - 内匠, 孝; 山内, 六男; 堀田, 康記; 高嶋, 秀隆; 笠村, 健一郎; 岡田, 光明; 勝又, 明敏 (Journal of Japanese Society of Oral Implantology, 2004)
The immediate or early loading method can shorten the duration of treatment with relevant satisfaction for patients. A 66-year-old female patient with completely edentulous mandible received four implants placed in the interforaminal area using CT images as the reference. Two weeks later, the implants were connected with a Dolder bar and loaded with an overdenture. Each implant was evaluated at the time of prosthetic loading and at every 2 months after initial prosthetic loading. At each follow-up visit, a panoramic radiograph was taken and the mobility of each implant was examined using the Periotest. Ahigher Periotest value than usual in one of the combination implants was obtained at 4 months after initial prosthetic loading and periimplant inflammation was suspected. However, periimplant bone loss was not observed in the radiograph. Six months after initial prosthetic loading, the Periotest value reduced to baseline and periimplant bone loss in the radiograph became clearly visible. This delay may be due to the latent stage of the inflammatory periimplant bone loss in the radiograph.